Stronger inhibitory effects of ticagrelor plus aspirin compared with clopidogrel plus aspirin on arachidonic acid induced platelet aggregation in patients with acute coronary syndrome with PCI (Journal of the Pakistan Medical Association, 2020)
Abstract Antagonists of the adenosine diphosphate (ADP) receptor, P2Y12 may inhibit platelet aggregation resulting from stimulation with arachidonic acid (AA). The potent P2Y12 blocker, ticagrelor has greater anti-platelet effects than clopidogrel. We explored the effects of ticagrelor versus clopidogrel on mean maximum aggregation ratios (MAR%) in response to AA stimulation in patients receiving conventional aspirin dosages. A total of 613 acute coronary syndrome (ACS) patients were followed from October 2017 to October 2018. At the 1- and 6-month follow-up visit, mean AA-MAR% was lower in the ticagrelor group when compared with the clopidogrel group (28.9% vs. 31.7%, 28.4% vs. 31.0%, P<0.001 and P=0.001, respectively). BARC1-2 bleeding occurred with greater frequency with ticagrelor rather than clopidogrel treated patients (29.3% vs. 9.5%, P<0.001; 23.5% vs. 9.3%, P<0.001). Excessive platelet inhibition and decreased AA-MAR% were considered the main reasons for the severe subcutaneous/dermal bleeding in ticagrelor treated patients. Continuous...